PENGARUH AIR KELAPA MUDA DAN EKSTRAK BAWANG MERAH TERHADAP PERTUMBUHAN STUM MATA TIDUR KARET (Hevea brasiliensis Muell Arg.) KLON PB 260 - Nazara, Marniati; Idwar, Idwar; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Rubert plant was one of important pantation comodity as second source of forign exchange after palm oil. This study aims to determine the interaction of young coconut water and red onion extract in accelerating the breakdown of stum buds in the sleeping eye of rubber plants and their growth.   This research was conducted in the experiement garden of faculty of agriculture of Riau University. This study was a factorial experiement using a completely randomized design, which consists of two factors, such as first factor is the concentration of young coconut water consisting of 0%, 25%, 50% and 75%, while the second factor is the concentration of shallot extract consisting of 0%, 1%, 2%, 3%.  Parameters observed were shoot growth time, shoot length, shoot diameter, number of leaves, shoot dry weight. Giving the concentration of 75% young coconut water and 2% shallot extract gave the best results on the growth of shoot length, number of leavers, bud diameter and ory weight of shoots from the stum rubber sleeping eyes.Giving 75% of young coconut water (containing cytokinin) and 2% onion extract (containing auxin) increases shoot length by 44.17 cm compared to without treatment of 10.33 cm Keywords:young coconut water,red onion extract,rubber sleeping eye stump